Covid-19 Prevention through Community Empowerment as an Effort to Reduce Stress Levels during the Implementation of the #Sesarengan Jogo Sleman Program - Maryana Maryana; Abiyyu Naufal Susanto (Health Notions, 2022)
People should be empowered such that they take responsibility for their health and follow a healthy lifestyle based on the health-promoting approach. With empowerment programs, it is hoped that people can face problems and tasks in their lives with a better control. This study was conducted to specify the correlation between community empowerment in Covid-19 prevention with stress level among Sleman citizen during the implementation of the #Sesarengan Jogo Sleman Program, an enforcement of restrictions on community activities program during Covid-19 pandemic by the government. This research was non-experimental study with a cross-sectional design and was conducted on July 6, 2021 until July 10, 2021. The questionnaire was distributed online. The population of this research were health workers at the puskesmas (health center), head of RT, head of RW, village apparatus, Bhayangkara trustees of community security and order (Babinkamtibmas), religious leaders/ community leaders, health cadre, and Sleman citizens. The sample size in this research were 568 people. Pearson product moment test were used for data analysis. The research results showed that the  r was -0.631 and the p-value was 0.000, it’s means that there was a strong, negative, and significant correlation between community empowerment in Covid-19 prevention and stress level. Community empowerment in Covid-19 prevention is a predictive variable to have a stress. Therefore, by increasing community empowerment in Covid-19 prevention, the stress level can be reduced. Keywords: Covid-19 prevention; community empowerment; stress level